Fructose Consumption in Pregnancy and Associations with Maternal and Offspring Hepatic and Whole-Body Adiposity in Rodents: A Scoping Review - Grace Zhao; Sarah Chondon; Clint Gray; Sheridan Gentili; Meagan Stanley; Timothy RH Regnault (Current Developments in Nutrition)
Background: Excess fructose consumption has been linked to adverse metabolic health, including impaired hepatic function and increased adiposity. The early life period, including preconception, pregnancy, and the newborn period, are critical periods in determining later metabolic health. However, the impact of excess fructose intake during this time on maternal, fetal, and offspring hepatic and whole-body adiposity, is not well defined. Objectives: To understand the effects of maternal fructose consumption pre- and during pregnancy on maternal, fetal, and offspring hepatic and whole-body adiposity. Methods: A systematic search of MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials was performed up to October 4, 2024, to identify animal and human studies that focused on maternal fructose consumption pre- and during pregnancy on hepatic and whole-body adiposity in the mother, fetus, and offspring. Citations, abstracts, and full texts were screened in duplicate. Hepatic adiposity was defined as elevated hepatic triglycerides or overall hepatic lipid accumulation. Whole-body adiposity was defined as increased adipose tissue, serum lipids, or adipocyte hypertrophy. Results: After screening 2538 citations, 37 experimental rodent studies reporting maternal fructose consumption pre- and during pregnancy in rodents were included. No human studies met the inclusion criteria. Prenatal fructose exposure was associated with maternal (9 of 12) and offspring (7 of 11) whole-body adiposity. A high proportion of studies (13 of 14) supported the association between fructose during pregnancy and increased maternal hepatic adiposity. Fetal hepatic adiposity and elevated expression of hepatic lipogenic proteins were noted in 4 studies. Offspring hepatic adiposity was supported in 16 of the 20 articles that discussed hepatic results, with 5 studies demonstrating more severe effects in female offspring. Conclusions: Fructose consumption during pregnancy in rodent models is associated with maternal, fetal, and offspring hepatic and whole-body adiposity with underlying sex-specific effects. No human studies met the inclusion criteria. Registration number: H8F26 on Open Science Framework (https://doi.org/10.17605/OSF.IO/H8F26)